2016
DOI: 10.15640/jeds.v5n2a6
|View full text |Cite
|
Sign up to set email alerts
|

Economic Impacts of Climate Change: Evidence from OIC Member Countries

Abstract: Recently, empirical studies have reported mixed findings on the impacts of parental migration on the academic performance of left-behind children. Although most of the studies suggested variation in parental involvement as the potential explanation for their findings, little is known about why parental involvement may differ among different left-behind households. Using a survey data collected from 401 caregivers of the left-behind children in rural areas of Niger State, Nigeria, we investigated the effects of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 30 publications
0
6
1
Order By: Relevance
“…The empirical nexus between governance measures and poverty alleviation is inconclusive (Sillah, 2016). The heterogeneous relationship could be attributed to the measurement of governance reliability (Evans & Ferguson, 2013) and the time length of the governance indicators on poverty alleviation (Grindle, 2004).…”
Section: Empirical Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…The empirical nexus between governance measures and poverty alleviation is inconclusive (Sillah, 2016). The heterogeneous relationship could be attributed to the measurement of governance reliability (Evans & Ferguson, 2013) and the time length of the governance indicators on poverty alleviation (Grindle, 2004).…”
Section: Empirical Literaturementioning
confidence: 99%
“…A research carried out by the World Bank ( 2008) indicates that countries with more advanced levels of governance can increase their national output and reduce the rate of infant mortality by 75%. Sillah (2016) reveals that good governance measures like corruption control and responsiveness contributes to poverty alleviation. Sebudubudu (2010) found that accountability and government responsiveness are paramount in transforming the economy and reducing poverty in Botswana.…”
Section: Empirical Literaturementioning
confidence: 99%
“…The World Bank shows the importance of governance from the perspective of aid in offering aid support (Moyo, 2009). More than just having money to reduce poverty, there is an increasing acknowledgment of governance, including restructuring social and political institutions (Moyo, 2009;Page & Pande, 2018;Sillah, 2016). Considering that the decentralization mechanism in Indonesia involves the delivery of proportional funding and authority to support development by the local governments, a significant difference in poverty eradication performance indicates a disparity in the local government's capability to plan and deliver suitable development programs.…”
Section: Introductionmentioning
confidence: 99%
“…Titeca (2012) refers to them as the socially and economically marginalized. According to Sillah (2019), they are people not included in the formal economy. As a result, the informal economic sector’s distinct economic and political dynamics offer a haven of protection for informal employees (Meagher, 2011; Sillah, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…According to Sillah (2019), they are people not included in the formal economy. As a result, the informal economic sector’s distinct economic and political dynamics offer a haven of protection for informal employees (Meagher, 2011; Sillah, 2019). In the past, informal workers have relied on the informal economy to prosper and support their families.…”
Section: Introductionmentioning
confidence: 99%